Penambahan Beberapa Jenis Tepung Serangga Pada Media Perbanyakan Jamur Metarhizium anisopliae (Metsch.) Sorokin Guna Meningkatkan Virulensinya Terhadap Hama Crocidolomia pavonana Fabricius di Laboratorium - Nizarrudin Aufa; Wildan Jadmiko (Jember University Press, 2023)
Crocidolomia pavonana is a significant pest in the Brassicaceae family. The study aimed to determine the effect of applying several types of insect flour to M. anisopliae growth media to increase its virulence against C. pavonana pests. The experimental design in this study used a completely randomized design (C.R.D.). The treatment used was A = 25 gr corn rice medium, B = 25 gr corn rice medium + 1.25 gr Hong Kong caterpillar flour, C = 25 gr corn rice medium + 3.75 gr Hong Kong caterpillar flour, D = 25 gr corn rice medium gr + 1.25 gr Kroto flour, E = 25 gr corn rice medium + 3.75 gr Kroto flour, F = 25 gr corn rice medium + 1.25 gr cricket flour, G = 25 gr corn rice medium + 3.75 gr cricket flour. The addition of insect flour could not increase the virulence of M. anisopliae against C. pavonana pests to above 50% due to less than optimal humidity conditions for M. anisopliae. The comparison of the types of insect flour used to be added to the propagation media did not significantly affect some of the parameters that had been observed, but on average, the M. anisopliae fungi propagation medium was added with insect flour made from Hong Kong caterpillars, namely treatment B (25 gr corn rice medium + 1.25 gr Hong Kong caterpillar flour) can cause the highest mortality against C. pavonana pests.